Study on a family with anderson–Fabry's disease and associated familial spastic paraplegia. Issue 6 (December 1976) - Pierides, A M; Holti, G; Crombie, A L; Roberts, D F; Gardiner, S E; Colling, A; Anderson, J
Abstract : A family in the north-east of England with Anderson–Fabry's disease is presented. Alpha-galactosidase activity in plasma and white cells was significantly reduced in three adult male members of the family. One of them had an abnormal chromosome karyotype pattern with an extra Y chromosome (47, XYY) and he was clinically less severely affected than his brothers. Coincidentally five other members of the family suffered from a form of familial spastic paraplegia.